Practical Considerations for Community-Based Health Promotion Events during the COVID- 19 Pandemic - Sarah E. Vordenberg; Heidi Diez; Caitlin Ferguson; Paul C. Walker; Jolene R. Bostwick; Kristin Klein (University of Minnesota Libraries Publishing, 2021)
Community-based health promotion events provide student pharmacists the opportunity to give back to the local community while simultaneously applying the knowledge and skills they are learning in the classroom (Accreditation Council for Pharmacy Education Standards 3, 4, and 12). In turn, community members receive benefits, such as receiving a vaccination and learning their blood pressure, as well as strategies to manage their health conditions. Traditionally, both individual community members and student pharmacists receive benefit. As a result of the coronavirus disease 2019 (COVID-19) pandemic, it is critical to consider the impact of public health via the local community when choosing to hold or suspend these activities. It is necessary to consider whether the benefits to individual community members who choose to participate (e.g., older adult with type 2 diabetes or underserved adults with limited access to the influenza vaccine) outweigh the risks to the public due to the pandemic. If there is sufficient benefit, there are practical considerations related to regulations, recruitment of community members, involvement of students and preceptors, location, supplies, delivery of patient care services, and activities after the event.